Pola Asupan Gizi Anak Usia Dini Pada Masa Pandemi COVID-19 - Hesti Novita Sari; Kristiana Maryani; Isti Rusdiyani (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2022)
The purpose of this study was to determine: (1) the nutritional intake of children aged 3 – 4 years during the covid-19 pandemic in Kubangawan Village, (2) ways parents provide nutritious food to chidren aged 3 – 4 tahun, (3) Factors that affect children who have malnutrition. This research is a qualitative research using descriptive. The subject in this study were the head of nutrition at the Ciruas public health center, parents of children aged 3 – 4 years. In the process of collecting data the researches used the metod of interview, observation, and documentation. While the validity test of the data used in the study were the persistence/consistency of observation, triangulation and member check. From the result of the study, it can be concluded that the nutritional intake or food that is often given to children aged 3 – 4 years is 4 healthy 5 perfect. Keywords: nutrition intake, children aged 3 – 4 years, covid-19 pandemic ReferencesCahyana, D. D. (2015). “Status Gizi Anak dengan Pertumbuhan dan Perkembangan Anak 0-2 Tahun di Wilayah Kerja Puskesmas Tomo Kabupaten Sumedang”. Jurnal Kesehatan Gizi , Vol.2 No.1. Desmita. (2016). Psikologi Perkembangan Anak. Bandung: Remaja Rosdakarya Offset. Dinar Nur Inten, A. N. (2019). "Literasi Kesehatan pada Anak Usia Dini melalui Kegiatan Eating Clean". Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 366-376, Vol 3,No 2. Endang, R. S. (2016). Pengaruh Gizi Terhadap Pertumbuhan Dan Perkembangan Anak. Jurnal Cakrawala Pendidikan, Vol 1, No 2. Hairuddin, A. (2018). “Penyakit Infeksi Dan Praktek Pemberian MP-ASI Terhadap Kejadian Stunting Pada Anak Usia 12-36 bulan”. Jurnal Dunia Gizi, Vol. 1, No.1, 53. Hidayat, F., Hidayat, I., Ghofur, A., & Setiawan Santoso, F. (2021). Penanganan Kesehatan Pasien Reaktif COVID-19 Melalui Terapi Zikir Dan Lingkungan Wawasan Pengalaman Subyektif. Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 11(1), 1–12. Huliyah, M. (2016). Hakikat Pendidikan Anak Usia Dini. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(1), 60–71. Idris, M. H. (2016). Karakteristik Anak Usia Dini . Jakarta: Luxima Metro Media. Imroatun, I. (2018). Alternatif Media Pengembangan Literasi Baca Tulis Berbahasa Nasional bagi Siswa Raudlatul Athfal AH-. Al Hikmah Proceedings on Islamic Early Childhood Education, 1(April), 103–112. http://conference.staialhikmahtuban.ac.id/index.php/ah-pieceImroatun, I., Hunainah, H., Rukhiyah, Y., & Apipah, I. (2021). Perbedaan Tingkat Pengenalan Huruf Hijaiyyah melalui Metode Iqro pada Anak Kelas A Taman Kanak-Kanak. Al-Mudarris (Jurnal Ilmiah Pendidikan Islam), 4(1), 23–40. https://doi.org/10.23971/MDR.V4I1.2975Indonesia, D. A. (2013). Al-Qur'an dan Terjemahannya. Jakarta: Bintang Indonesia. Jaya, I. (2018). Penerapan Statistik Untuk Pendidikan. Medan: Perdana Publishing. Khairieri, H. K. (2018). "Karakteristik Perkembangan Anak Usia Dini Dari 0-6 Tahun". Jurnal Warna, Vol.2 No.2. Maleong, L. J. (2011). Metodologi Penelitian Kualitatif. Bandung: PT Remaja Rosdakarya. Matondang, Z. (2013). Statiska Pendidikan. Medan: Unimed Press. Miles Matthew B, E. a. (2014). Qualitative Data Analysis, A Methods Source, Edisi 3. USA: sage publication. Terjemahan Tjetjep Rohindi Rohidi. Jakarta: UI Press. Muhammad, H. (2017). Penilaian Status Gizi. Jakarta: Buku Kedokteran. Mulyasa, H. (2012). Manajemen Paud. Bandung: PT. Remaja Rosdakarya. Nasruddin, M., Sriwinarsih, E., Rukhiyah, Y., Supriyanti, S., & Khasanah, N. (2021). Pengaruh Pendidikan Agama Islam Di Sekolah Terhadap Perilaku Anak Di Rumah Studi Kasus TK Aisyiyah 5 Kota Magelang. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 6(1), 77–88. Nurani, S. d. (2013). Gizi Anak Dan Remaja. Jakarta: Universitas Terbuka. Nurhayati, R. (2019). Membangun Budaya Literasi Anak Usia Dini dalam Keluarga. Nuansa Akademik: Jurnal Pembangunan Masyarakat, 4(1), 79–88. https://doi.org/10.47200/JNAJPM.V4I1.918Pandoman, A. (2020). Analisis Quietus Politik Terhadap Upaya Pemerintah Menangani Wabah Covid-19 Pasca Deklarasi Public Health Emergency Of International Concern (PHEIC). Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 10(1), 1–12. https://doi.org/10.47200/ulumuddin.v10i1.379Anies, P. M. (2020). Covid 19 : Seluk Beluk Corona Virus Yang Wajib Di Baca. Yogyakarta: Arruz Media. Purwani, E. (2013). (erni_purwani@ymail.com) "Pola Pemberian Dengan Status Gizi Anak Usia 1-5 Tahun Di Kabunan Taman Pemalang”. Email kepada Mery Chalista (mary_chalista81@yahoo.co.id) Septikasari, M. (2018). Status Gizi Anak Dan Faktor Mempengaruhi. Yogyakarta: UNY Press. Setiawati, et al. (2020). “Hubungan Status Gizi Dengan Pertumbuhan Dan Perkembangan Balita 1-3 Tahun”. Jurnal Kesehatan, Vol 14, (1). Sugiono. (2017). Metode Penelitian Kuantitatif, Kualitatif, Dan R&D. Bandung: Alfabeta. Syahrum, & S. (2015). Metodologi Penelitian Kualitatif. Bandung: Citapustaka. T Voortman, K. B, et al. (2016). Protein intake in early childhood and body composition at the age of 6 years : The Generation R Study. International Journal of Obesity , 1018–1025. Wiko Saputra, R. H. (2012). "Faktor Demografi Dan Risiko Gizi Buruk Dan Gizi Kurang". Jurnal Makara Kesehatan, Vol 16, (2). Wirjatmadi, M. A. (2014). Gizi Dan Kesehatan Balita. Jakarta: Kencana Prenada Media Group. Yuliana. (2020). Corona Virus Diseases (Covid-19) . Fakultas Kedokteran: Universitas Lampung, 187-192, Vol 2, No 2. Yuliani Nurani, S. M. (2013). Konsep Dasar Pendidikan Anak Usia Dini. Jakarta: Indeks. Yusri. (2013). Statistika Sosial. Yogyakarta: Graha Ilmu.